ENZYME MIMICS BASED ON CYCLIC PORPHYRIN OLIGOMERS - STRATEGY, DESIGN AND EXPLORATORY SYNTHESIS - Anderson, H; Sanders, J (1995)
A strategy is set out for the design and synthesis of a series of cyclic porphyrin oligomers which should be able to bind two or more substrate molecules, catalyse a reaction between them and release the product(s). Exploratory syntheses and some spectroscopic properties of butadiyne-linked cyclic dimer, trimer and tetramers of two meso-diaryl porphyrins are described in detail.